IP@Remote : intelligent photography remote (With Arduino & Android) - Han, Weizhi (2017)
There is a niche market for high speed photography, with products made specifically to address this particular area of photography. One common issue is that these products tend to be limited in their functionalities, coming equipped with only a small handful of sensors and functions. With no ability to expand to other methods of sensing, users sometimes have to come up with workarounds to situations where the hardware provided is not adequate. This project is aimed at addressing this problem, by building a hardware and software application that is expandable to many situations. Through the use of Arduino and Android programming, the Intelligent Photography remote is aimed at providing an all-in-one solution to high speed photography needs, with the added functionality of being a remote trigger. The Android application will be providing the graphical interface for this project, communicating with the Arduino hardware. It will control all functionalities available, allowing the Arduino to only monitor the situation and trigger the camera and/or flash.